Modi magic: The nudge theory, India, Pakistan, China and more - Varma, Ashali (Gurugram Garuda Prakashan, 2024)
From Swachh Bharat to UPI payments, to sanitation and to Jammu and Kashmir so much else has been achieved in the last decade in India. More, I would say, than in the last 70 years before, and in contrast, compare this with how China and Pakistan lost out...Check out this collection of astute articles from the pen of a veteran journalist who has watched, worked and reported from around the globe.
Keywords: Prime Minister; Narendra Modi; Indian Foreign Policy